Modeling the ecology and evolution of biodiversity: Biogeographical cradles, museums, and graves - Rangel, Thiago F; Edwards, Neil R; Holden, Philip B; Diniz-Filho, José Alexandre F; Gosling, William D; Coelho, Marco Túlio P; Cassemiro, Fernanda A S; Rahbek, Carsten; Colwell, Robert K (Science (American Association for the Advancement of Science), 2018)
Individual processes shaping geographical patterns of biodiversity are increasingly understood, but their complex interactions on broad spatial and temporal scales remain beyond the reach of analytical models and traditional experiments. To meet this challenge, we built a spatially explicit, mechanistic simulation model implementing adaptation, range shifts, fragmentation, speciation, dispersal, competition, and extinction, driven by modeled climates of the past 800,000 years in South America. Experimental topographic smoothing confirmed the impact of climate heterogeneity on diversification. The simulations identified regions and episodes of speciation (cradles), persistence (museums), and extinction (graves). Although the simulations had no target pattern and were not parameterized with empirical data, emerging richness maps closely resembled contemporary maps for major taxa, confirming powerful roles for evolution and diversification driven by topography and climate.